Liposome interaction with macrophages and foam cells for atherosclerosis treatment : effects of size, surface charge and lipid composition - Tang, Jinkai (2021)
Liposomes are potential drug carriers for atherosclerosis therapy due to low immunogenicity and ease of surface modifications that allow them to have prolonged circulation half-life and specifically target atherosclerotic sites to increase uptake efficiency. However, the effects of their size, charge, and lipid compositions on macrophage and foam cell behaviour are not fully understood. In this study, liposomes of different sizes (60 nm, 100 nm and 180 nm), charges (−40 mV, −20 mV, neutral, +15 mV and +30 mV) and lipid compositions (1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine, 1,2-dipalmitoyl-sn-glycero-3-phosphocholine, L-a-phosphatidylcholine, and egg sphingomyelin) were synthesized, characterized and exposed to macrophages and foam cells. Compared to 100 nm neutral 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) liposomes, flow cytometry and confocal imaging indicated that cationic liposomes and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DSPC) liposomes were internalized more by both macrophages and foam cells. Through endocytosis inhibition, phagocytosis and clathrin-mediated endocytosis were identified as the dominant mechanisms of uptake. Anionic and DSPC liposomes induced more cholesterol efflux capacity in foam cells. These results provide a guide for the optimal size, charge, and lipid composition of liposomes as drug carriers for atherosclerosis treatment.